2008
DOI: 10.1371/journal.pone.0003911
|View full text |Cite
|
Sign up to set email alerts
|

Human Gene Coexpression Landscape: Confident Network Derived from Tissue Transcriptomic Profiles

Abstract: BackgroundAnalysis of gene expression data using genome-wide microarrays is a technique often used in genomic studies to find coexpression patterns and locate groups of co-transcribed genes. However, most studies done at global “omic” scale are not focused on human samples and when they correspond to human very often include heterogeneous datasets, mixing normal with disease-altered samples. Moreover, the technical noise present in genome-wide expression microarrays is another well reported problem that many t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
179
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(186 citation statements)
references
References 32 publications
6
179
0
Order By: Relevance
“…Genes with similar function or that participate in the same pathway often have correlated patterns of gene expression (Prieto et al 2008;Roider et al 2009;Khatri et al 2012;Hormozdiari et al 2015). In the GTEx TWNs, we observed enrichment of edges between transcription factors and known target genes (Supplemental Methods; Supplemental Fig.…”
Section: Coregulation Of Expression and Isoform Ratios Reflects Biolomentioning
confidence: 95%
“…Genes with similar function or that participate in the same pathway often have correlated patterns of gene expression (Prieto et al 2008;Roider et al 2009;Khatri et al 2012;Hormozdiari et al 2015). In the GTEx TWNs, we observed enrichment of edges between transcription factors and known target genes (Supplemental Methods; Supplemental Fig.…”
Section: Coregulation Of Expression and Isoform Ratios Reflects Biolomentioning
confidence: 95%
“…To estimate the quality of the clustering solution obtained by HCCA, we clustered the HRR network using the MCL algorithm with a range of different inflation values (Supplemental Table S1). In addition, we included clustering solutions for MCODE (Bader and Hogue, 2003;Prieto et al, 2008), performed clustering using k-means with different settings (Hartigan and Wong, 1979), and then compared the results obtained from the HCCA with the different clustering solutions for the other algorithms ( Fig. 3; Supplemental Table S1).…”
Section: Estimates Of Clustering Solutionsmentioning
confidence: 99%
“…15 Some other ribosomal proteins have also been shown to be involved in the apoptotic process, including RPS19, RPS3a and RPS29, via Bcl2 or p53 related mechanisms. 16 In this work, directed by the cDNA microarray analysis, pathway, Gene Ontology (GO) and Gene-RegulatoryNetwork (GenRelNet) analyses, [17][18][19] we demonstrated that the inhibition of NF-jB activity and down-regulation of its target gene Gadd45b contributed to MPS-1 knockdowninduced apoptosis of gastric cancer cells.…”
mentioning
confidence: 86%